Gestión de Riesgos Laborales en el área Eurolit de la empresa TUBASEC C.A.: Plan de Mitigación. - Minta Morales, Mayra Elisa (2015)
Tubasec CA, in the production process of manufacturing fiber cement corrugated sheets using various raw materials, equipment, machines, tools and other work tools as well as working methods and procedures that may pose risks or generate at the time of execution and can materialize in incidents, accidents or illness if you have not taken the necessary technical and organizational measures to control or mitigate risk. These risks are related to risk factors: mechanical, physical, chemical, biological, ergonomic and psychosocial; its management and control; as well as the training and information of workers level.